Hill Women in the Time of Tribal Wars: A Reading of Folk Tales from Northeast India - Gorai, Chaitali (The Grove - Working Papers on English Studies, 2023)
What we know about women in traditional tribal societies in Northeast India is based on what oral traditions tell us about them. Although they were more resourceful and respected than the women of the plains societies, their disadvantages in a world teeming with tribal feuds were considerable. Ruthless enemies destroyed villages and killed everyone, but sometimes they spared the lives of women. When two hostile villages agreed to a truce, the women enjoyed freedom of movement, but only within the village. Kidnappings were frequent, and it was unsafe for women to leave the village unaccompanied by men. Their vulnerability prompted tribes to adopt measures such as face tattooing and the practice of tribe or village endogamy. Based on the evidence in oral traditions, mostly folk tales, this paper reconstructs the position of women in the tribal societies of Northeast India during the period of inter-tribal wars.